Be incredibly creative 52 brilliant little ideas for honing your mind - Bevan, Rob (The Infinite Ideas, 2007)
Many of us want to improve our creative skills. There's tons of advice out there to help us - a never-ending avalanche of books, magazine, websites and TV programmes. This book, in the '52 Brilliant Little Ideas' series, cuts straight to the heart of the issue. The authors provide practical and inspiring advice.